Antara Validitas dan Inspirasionalitas: Wacana Historis Diaspora Minang di Bali - Sawirman Sawirman (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
This article describes the historical discourse of Minang diaspora in Bali particularly the discourse that inspired them come to Bali, the history of their arrival, the relationship between Pemecutan Palace in Denpasar and Minang people, and the levels of validity of facts and sources. Data were taken from existing documents, interviews with Minang community leaders in Bali, and meetings held by the Minang community in Bali. The Discourse-Historical Approach (DHA) was used to analyze the data. Several interpretations can be stated. The cultural, survival, and ideological discourses inspired the Minang people come to Bali. These discourses have a collective memory status. A number of discourses with the level of cold facts, individual memories, and inferences are the first arrival of Minang people to Bali and the relationship between Pemecutan Palace and Minang people.